A SO2F2 mediated mild, practical, and gram-scale dehydroxylative transforming primary alcohols to quaternary ammonium salts. Issue 33 (16th August 2019) - Zhao, Chuang; Zha, Gao-Feng; Fang, Wan-Yin; Alharbi, Njud S.; Qin, Hua-Li
Abstract: A simple, practical and gram-scale process for direct transformation of primary alcohols or silyl ethers to ammonium salts was developed. This method has the feathers of easy work-up (a simple filtration), mild condition, high yield, great practicality and robustness. And the application of the ammonium salts in Suzuki coupling reaction was also accomplished. Graphical abstract: Image 1 Highlights: A simple, practical and gram-scale process for direct transformation of alcohols or silyl ethers to ammonium salts. Easy work-up (a simple filtration), mild condition, high yield, great practicality and robustness. Application of the ammonium salts in Suzuki coupling reaction.